Simple Additive Weight in Placement of Community Service Program Student Locations - N Pandiangan; M Lintang; BA Priyudahari (Technium Social Sciences Journal, 2023)
Community Service Program is a mandatory activity for student to implement the Tree Pillars of Higher Education as well as being a creative and innovative space for students to cannel knowledge and knowledge to find a solution for problems faced by the village community. It is hoped that the placement of the location of the community service program students will be right on target and not be a polemic for Community Service Program students who feel infair with the distribution of locations. The selection of Community Service Program locations for students in this case study uses the Simple Additive Weight (SAW) Algorithm by reviewing several student criteria, such a students having babies, student health conditions, wheather the student is pregnant or not, students have a vehicle or not, where students live, Grade Point Average (GPA) of students, organizational participation, taking courses, field experience practice, as well as the criteria for the location of the Community Service Program is the location of the Community Service Program, illiteracy, population density, and village area. The results of ranking using SAW, , the results obtained for student 1 with a value of 5.866667 are suggested to occupy Village 1 with a value of 2.833333, Student 2 with a value of 7.133333 occupies Village 2 with a ranking value of 2.916667, and Student 3 with a value of 7.2 occupies Village 3 with a value of 3.75.